Clinical performance of whitening on devitalized teeth: A retrospective observational study - Correia, Ayla Macyelle de Oliveira [UNESP]; Matos, Felipe de Souza [UNESP]; Huhtala, Maria Filomena Rocha Lima [UNESP]; Bresciani, Eduardo [UNESP]; Caneppele, Taciana Marco Ferraz [UNESP] (Editora Cubo, 2020)
Objective: This retrospective observational study evaluated the clinical performance of intracoronal whitening and correlated the main factors that interfere with its stability and patient satisfaction. Material and Methods: The paper was designed following the STROBE statement. Patients from the Institute of Science and Technology-ICT/UNESP database who underwent nonvital tooth whitening from August 2010 to July 2015 were selected. Data collection was performed by researching the institution records, patients interview, clinical and radiographic examination. Data were analyzed using Mann-Whitney test and Spearman’s correlation (p < 0.05). Results: The initial search on 1275 records resulted in 43 patients, of whom 18 were selected according to eligibility criteria. There was positive correlation only between the degree of patient’s satisfaction and the perception of color difference after whitening treatment (p < 0.05). Color relapse was observed in all conditions, independently of the period of follow-up (p > 0.05). There was no case of external cervical root resorption. Conclusion: Color changes after whitening influenced patient’s satisfaction. There was no correlation among the color relapse and height of gutta-percha, return interval or cause of darkening.
Desempenho clínico do clareamento em dentes desvitalizados: Estudo observacional retrospectivo
Keywords: Tooth discoloration; Tooth nonvital; Tooth whitening